Multimodal teaching practices for the development of literacy competencies in basic education - García Lebroc, Lázaro Adrián; Manzano Díaz, Mirtha; Bravo Alvarado, Rufina Narcisa; Vargas Castro, Karina Verónica (Revista de Ciencias Sociales, 2026)
The development of skills that enable students to produce written work based on reading is fundamental to academic performance and comprehensive education, especially in early childhood and elementary education. The objective of this study is to describe the multimodal strategies for developing literacy skills applied by elementary school teachers. Using a qualitative approach and phenomenological design, open-ended interviews were conducted with intentionally selected elementary school teachers in Zone 5 of Ecuador. The guide was organized into socio-emotional-affective and cognitive-instrumental dimensions. The results showed that multimodal teaching practices enhance literacy skills by integrating playful activities, gamification, positive feedback, and socio-emotional support, identifying that emotion management, based on respect, empathy, and communication, promotes school engagement and self-regulation. In reading, the pre-reading, reading, and post-reading phases strengthen comprehension and critical thinking. Likewise, the habit of reading is sustained through regular routines, the selection of texts of interest, and the use of visual resources. It is concluded that the integration of methodologies that combine reading motivation with the development of cognitive and metacognitive skills is essential for strengthening reading and writing competencies.